Radiation refrigeration coating for fabric and preparation method thereof
By using thermal expansion microspheres with rutile titanium dioxide as the core in the fabric coating, the existing coating has solved the problem of poor temperature reduction and insufficient toughness in the sunshine environment, and achieved high-performance radiation refrigeration and good adhesion coating, which improved the overall performance of the fabric.
Patent Information
- Application Number
- CN202411961887.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
The existing fabric coatings have poor temperature reduction effects in strong sunshine environments, and the flexible substrate coatings have problems such as insufficient toughness, easy cracking and poor adhesion.
Thermal expansion microspheres with rutile titanium dioxide as the core are used to prepare core-shell structure functional fillers through suspension polymerization technology, combined with aqueous resin emulsion and additives, and form a high-performance radiation refrigeration coating to improve the flexibility and adhesion of the coating.
The high-performance radiation refrigeration function of the coating is realized, which improves the flexibility and adhesion of the fabric, improves the cooling effect and durability of use.
Smart Images

Figure CN119663649A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional fabric coating materials, and in particular relates to a radiation cooling coating for fabric and a preparation method thereof. Background Art
[0002] Fabric radiant cooling coating is an advanced technology that aims to reduce the temperature of the fabric surface by reflecting sunlight and emitting infrared radiation, thereby achieving a cooling effect.
[0003] The existing fabric coatings are often used in strong sunlight environments, but the cooling effect is poor due to insufficient reflectivity of sunlight. In addition, the coatings of flexible substrates (fabrics) generally have the problem of poor durability due to insufficient toughness, easy cracking, and poor adhesion. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a radiation cooling coating for fabrics and a preparation method thereof. Aiming at the requirements of cooling and flexibility of fabric base fabrics, the present invention uses thermal expansion microspheres with rutile titanium dioxide as the core to achieve high-performance radiation cooling function of the coating, as well as good toughness and adhesion properties.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A radiation cooling coating for fabrics, the raw materials of which are composed of water-based resin emulsion, core-shell structure functional filler, additives and water;
[0008] The core-shell structure functional filler is a heat-expandable microsphere with rutile titanium dioxide and low-boiling-point alkane as the core and acrylonitrile-methyl methacrylate copolymer or acrylonitrile-methacrylonitrile copolymer as the shell.
[0009] The heat-expandable microsphere of the present invention is a polymer core / shell particle, in which a volatile alkane compound is encapsulated by a thermoplastic shell. When the microsphere is heated, it expands to significantly increase its volume, and this increase in volume is maintained after cooling to room temperature. The preparation process of the heat-expandable microsphere with rutile titanium dioxide as the core is based on suspension polymerization technology. The organic phase is mainly composed of monomers, low-boiling alkane foaming agents, rutile titanium dioxide powder, initiators and crosslinking agents; the aqueous phase contains inorganic stabilizers and surfactants. The two phases are mixed by high-speed dispersion to form an emulsion, in which the organic phase is dispersed in water in the form of small droplets. The stabilizer and surfactant prevent them from agglomerating by encapsulating these tiny droplets. As the temperature rises to the temperature at which the initiator starts to initiate polymerization, the monomer undergoes a polymerization reaction. Since the polymer is insoluble in the organic phase, it moves to the phase interface, i.e., the water / organic interface, and forms a shell on the surface of the microsphere. As the polymer shell is formed, the rutile titanium dioxide and the liquid foaming agent are encapsulated inside the microsphere. Depending on the type of monomer and blowing agent used, different heat treatment processes are required to thermally expand the microspheres. When heated to a temperature that precisely matches the polymer glass transition temperature (Tg) and the boiling point and / or expansion characteristics of the blowing agent, the polymer shell softens, the blowing agent vaporizes, and the internal pressure causes the microspheres to expand to several times their original volume while the weight remains unchanged. Finally, the temperature is lowered to below the Tg of the polymer shell, the shell hardens, and the thermally expandable microspheres with rutile titanium dioxide and low-boiling alkane as the core are prepared.
[0010] The ability of the microspheres to thermally expand is highly dependent on the barrier properties of the polymer shell enclosing the core material and the mechanical properties of thermal deformation during expansion. The barrier properties of the polymer shell involve two aspects: first, the polymer shell is formed in situ during the polymerization process, which requires the shell to be thick and defect-free to ensure that it does not affect the encapsulation of the rutile titanium dioxide powder and the alkane; second, the cohesive properties of the polymer constituting the shell are very important to prevent the alkane from penetrating through the shell. During the thermal expansion process, the thickness of the polymer shell is significantly reduced, further highlighting the importance of barrier properties compared to before expansion.
[0011] When the barrier properties of the shell are sufficient to prevent rutile titanium dioxide and alkanes from escaping from the microspheres, the expansion of the microspheres depends on the viscoelastic properties of the polymer shell. In order for the microspheres to expand, the internal pressure must overcome the yield strength of the polymer shell. The glass transition temperature (Tg) of the polymer shell is the basic parameter that determines the expansion temperature of the microspheres. Below Tg, the shell is rigid and the microspheres cannot expand. Near Tg, the polymer shell softens and the ductility increases, so the microspheres can expand. The polymer that constitutes the microsphere shell has the ability to expand several times in volume through plastic flow deformation. Important factors that affect the ductility of the polymer shell include chemical composition, molecular weight, degree of crosslinking, and crystallinity.
[0012] The homopolymer of acrylonitrile (AN) monomer is semi-crystalline and has excellent barrier properties; however, its thermoplasticity is insufficient, so the present invention uses acrylonitrile and methyl methacrylate (MMA) or methacrylonitrile (MAN) monomers to copolymerize to form a polymer shell.
[0013] Preferably, the rutile titanium dioxide is organically coated surface-modified rutile titanium dioxide, which is easier to disperse in the organic phase.
[0014] Preferably, the low boiling alkane is isopentane or isooctane. Different alkanes have different expansion properties, and not only the boiling point is important, but also the structure of the alkane is important. The present invention finds that highly branched alkanes exhibit better expansion properties than linear or cyclic structures with similar boiling points. The thermal expansion properties of highly branched isopentane (boiling point 27.7°C) and isooctane (boiling point 99.3°C) are suitable for use as the core foaming agent of the present invention.
[0015] Preferably, the aqueous resin emulsion is one of an aqueous polyurethane emulsion and an aqueous acrylic elastic emulsion. The coating film-forming material adopts an aqueous polyurethane emulsion, which has excellent flexibility and wear resistance, strong adhesion to the substrate, and a soft and smooth film. Aqueous acrylic elastic emulsion can also be used, which has good flexibility, elongation and tensile strength through low glass transition temperature and special molecular structure design, and improves coating cracking; preferably, an elastic emulsion with ultraviolet and chemical double crosslinking is used, and the monomers in the emulsion will further undergo polymerization reaction under ultraviolet light, effectively increasing the crosslinking density of the coating, improving the surface density, and making the coating have excellent crack resistance, early wet adhesion, water resistance and stain resistance.
[0016] Preferably, the auxiliary agent includes at least one of a wetting agent, a defoaming agent, a pH regulator, a film-forming aid, a thickener, a leveling agent and an adhesion enhancer.
[0017] The additive of the present invention contains an organosilicon defoamer, which can quickly break bubbles by bridging the foam liquid film. The low surface tension of the defoamer droplets pushes the organosilicon to continuously flow into the adjacent bubble liquid film, continuously and repeatedly breaking bubbles, and has a long-term and lasting foam suppression effect. The present invention improves the dispersion effect of functional fillers and the overall production efficiency in the coating production process by effectively controlling bubbles, and improves the density and appearance of the coating after construction.
[0018] To further improve the adhesion between the coating and the substrate, an adhesion enhancer may be added, preferably a water-based silane coupling agent, to improve the adhesion of the resin coating to the substrate, improve the binding force of the filler in the resin, and improve the water resistance and durability of the coating itself.
[0019] The invention adopts a free radical suspension polymerization method to prepare a core-shell structure functional filler (i.e. a core-shell structure thermal expansion microsphere), wherein acrylonitrile and methyl methacrylate or methacrylonitrile are used as monomers, rutile titanium dioxide is used as a core material, a low-boiling-point alkane is used as a core foaming agent, 1,4-butanediol dimethacrylate is used as a crosslinking agent, diisopropylbenzene peroxide is used as an initiator, magnesium hydroxide is used as an inorganic stabilizer, and 2-ethylhexyl sulfate sodium salt is used as a surfactant.
[0020] Preferably, the method for preparing the core-shell structure functional filler comprises the following steps:
[0021] Dissolve sodium hydroxide in water, add a magnesium chloride aqueous solution containing 2-ethylhexyl sulfate sodium salt, stir vigorously (speed is 1500r / min) to obtain a magnesium hydroxide dispersion, then add sodium nitrite and polyvinyl pyrrolidone, stir evenly to obtain an aqueous phase;
[0022] acrylonitrile and methyl methacrylate or methacrylonitrile are mixed, and then 1,4-butanediol dimethacrylate, diisopropylbenzene peroxide, low-boiling alkane and rutile titanium dioxide are added, and stirred evenly to obtain an organic phase;
[0023] The organic phase is mixed with the aqueous phase, dispersed evenly at high speed, heated and pressurized to react, and discharged after cooling;
[0024] The pH value of the product obtained by discharging is adjusted to acidic, and the product is washed, filtered, dried and foamed to obtain the core-shell structure functional filler.
[0025] Preferably, the temperature of the foaming treatment is 110-130° C., and the time is 1-2 min.
[0026] Preferably, the molar ratio of sodium hydroxide to magnesium chloride is 2 to 2.1:1; and / or
[0027] The mass ratio of water, sodium hydroxide, sodium salt of 2-ethylhexyl sulfate, sodium nitrite and polyvinyl pyrrolidone in the aqueous phase is 100: 2-4: 0.1-1.5: 0.01-0.5: 0.1-1; and / or
[0028] In the mixture of acrylonitrile, methyl methacrylate or methacrylonitrile and 1,4-butanediol dimethacrylate, the molar fraction of acrylonitrile is 55-65 mol % and the molar fraction of 1,4-butanediol dimethacrylate is 0.05-0.2 mol %; and / or
[0029] The mass ratio of acrylonitrile, dicumyl peroxide, low boiling point alkane and rutile titanium dioxide in the organic phase is 20-30: 0.1-0.5: 2-15: 5-17; and / or
[0030] The volume ratio of the organic phase to the aqueous phase is 1:1.2-3; and / or
[0031] The pH value is adjusted to acidity by using 10 wt % dilute sulfuric acid or dilute hydrochloric acid to adjust the pH value to 2-3, so as to remove the magnesium hydroxide suspension stabilizer deposit on the surface of the microspheres.
[0032] Preferably, the process of mixing the organic phase and the aqueous phase, dispersing them uniformly at high speed, and then reacting them under heating and pressurization conditions is as follows: pouring the dispersed material into a reactor, sealing it, deoxygenating it with nitrogen and pressurizing it to 0.4-0.6 MPa, heating it to 62° C. while maintaining stirring to react, reacting for 24 hours, cooling it to room temperature to terminate the polymerization reaction, and discharging the material.
[0033] The present invention adopts a hollow structure design of heat-expandable microspheres with rutile titanium dioxide as the core, and relies on the huge refractive index difference between the ultra-high refractive index of rutile titanium dioxide 2.73 and the surrounding hollow medium with a refractive index as low as 1, which can efficiently reflect ultraviolet (UV), visible light (Vis) and near-infrared light (NIR) in sunlight, thereby reducing heat absorption. At the same time, the polymer material of the shell layer of the heat-expandable microspheres can radiate the heat of the object in the infrared band. This process can be effectively carried out through the atmospheric window (within the wavelength range of 8 to 13 μm) because the atmosphere absorbs less infrared radiation in this band. The radiation cooling coating of the present invention can be widely used in outdoor equipment such as clothing, fabrics used in high temperature environments, etc., and can reduce the temperature of materials such as clothing, tents, tarpaulins, awnings, etc. used outdoors under sunlight.
[0034] The second technical solution of the present invention:
[0035] The present invention also provides a method for preparing the radiation cooling coating for fabrics, comprising the following steps:
[0036] Accurately weigh the raw materials according to their weight, add the core-shell structure functional filler into water, add the water-based resin emulsion and the additive under stirring, and obtain the coating;
[0037] The coating is applied onto a flexible substrate and dried to obtain a radiative cooling coating.
[0038] Preferably, the radiation cooling coating for fabrics comprises, by weight, 30 to 60 parts of aqueous resin emulsion, 30 to 60 parts of core-shell structure functional filler, 1 to 10 parts of auxiliary agent and 5 to 40 parts of water.
[0039] Preferably, the coating amount on the flexible substrate is 0.2-0.6 kg / m 2 .
[0040] Preferably, the flexible substrate comprises at least one of a fabric and a coated fabric.
[0041] The fabric is made of yarn through weaving or knitting process, including pure textile fabric, blended fabric, mixed fabric, interwoven fabric; the fabric can also be a non-woven fabric made by directional or randomly arranged fibers combined with each other through friction, cohesion, or bonding, or a combination of these methods. The fibers include natural fibers and chemical fibers. Natural fibers include plant fibers (such as cotton and linen) and animal fibers (such as wool and silk); chemical fibers include artificial fibers (such as viscose fibers) and synthetic fibers (such as polyester and nylon). The yarn is made of fiber through spinning process, which can be pure spinning yarn, blended yarn, accompanying spinning yarn, and can also be divided into uniform mixed yarn, variable mixed yarn, combination or composite yarn according to the distribution of mixed fibers. The coated fabric refers to a fabric that is coated with polyvinyl chloride (PVC), polyurethane (PU), polyacrylate (PA) and other coatings on the base fabric through a coating process to enhance its functionality and have additional properties.
[0042] More preferably, the fabric is a flexible substrate such as woven fabric, knitted fabric, or non-woven fabric. The coated fabric includes polyurethane (PU) or polyvinyl chloride (PVC) coated fabric.
[0043] The present invention does not limit the method of applying the coating to the substrate, as long as the purpose of uniformly applying the coating to the substrate is achieved. For example, the coating can be applied to the surface of the substrate by spraying, roller coating or dipping. The spraying can be performed by an air sprayer, and the coating is fully atomized and then sprayed on the substrate. The appearance is smooth and beautiful. It can be sprayed 2 to 3 times according to actual needs. The roller coating process uses a roller coater, which rotates the roller in the coating tank to adhere the coating, and then transfers it to the surface of the flat substrate to form a continuous coating film, which is easy to realize continuous operation and has high production efficiency. The dipping process is the simplest and most flexible. The flexible substrate is directly immersed in the coating, and the soaking time is controlled and then taken out and dried.
[0044] The radiation cooling coating for fabrics of the present invention is coated on the surface of a substrate by spraying, roller coating, dipping and other processes. The fabric with the radiation cooling coating can be used for outdoor sun protection and cooling, and also has a waterproof function.
[0045] Compared with the prior art, the present invention has the following advantages and technical effects:
[0046] 1. Excellent radiation cooling performance: The hollow structure of the core-shell structured thermal expansion microspheres and the large refractive index contrast of the rutile titanium dioxide core cause a strong scattering effect on sunlight, thus having outstanding radiation cooling performance.
[0047] 2. Improve the flexibility and feel of fabrics: Heat-expandable microspheres can provide softness and elasticity in fabric coatings, making the fabric feel more comfortable and also improving the appearance quality.
[0048] 3. Reduce fabric weight: Since the hollow structure formed by the heat-expandable microspheres after thermal expansion has a very low density, the weight of the fabric can be reduced.
[0049] 4. Improve the waterproofness and durability of fabrics: The filled heat-expandable microspheres help the coating to expand and contract with the flexible substrate through high elasticity, and form a protective barrier to prevent water penetration. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0051] Figure 1 The outdoor cooling performance of the radiation cooling coatings of different PVC and PU fabrics in Examples 1 to 3;
[0052] Figure 2 The outdoor cooling performance of the woven fabric radiant cooling coating in Example 4. DETAILED DESCRIPTION
[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0054] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0055] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0056] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0057] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0058] It should be pointed out that the "fabric" in the present invention is a broad concept used in the clothing, furniture and decoration industries, including all types of fabrics, such as coated fabrics.
[0059] It should be pointed out that the parts not described in detail in the present invention are conventional operating methods in the art and are not the focus of the present invention. For example, specific methods such as spraying, roller coating or dipping processes are all completed by conventional methods. For example, those skilled in the art can adjust the selection and dosage of coating additives including wetting agents, defoamers, pH adjusters, film-forming agents, thickeners, leveling agents and adhesion enhancers according to actual needs.
[0060] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0061] All raw materials used in the embodiments of the present invention are purchased from the market. For example, PVC coated fabric and PU coated fabric 1 were purchased from Shenzhen Baixin Textile Co., Ltd.; PU coated fabric 2 was purchased from Dongguan Junlifeng Textile Leather Co., Ltd.; woven fabric was purchased from Wuxi Zhongshui Geotechnical New Materials Co., Ltd.; non-woven fabric was purchased from Jiangmen Hongxiang Non-woven Fabric Co., Ltd.
[0062] Unless otherwise specified, the “parts” used in the embodiments of the present invention are “parts by weight”.
[0063] The technical solution of the present invention is further illustrated by the following embodiments.
[0064] Example 1
[0065] 1. Preparation of thermally expandable microspheres with rutile titanium dioxide as the core
[0066] Preparation of aqueous phase: 3.4 g of NaOH was completely dissolved in 50 mL of deionized water, and then an aqueous solution containing 1.0 g of 2-ethylhexyl sulfate sodium salt, 8.4 g of magnesium chloride (MgCl2·6H2O), and 50 mL of deionized water was added under stirring (speed of 400 r / min), and then stirred vigorously (speed of 1500 r / min) for 30 minutes to obtain a relatively stable magnesium hydroxide dispersion, and then 0.05 g of sodium nitrite and 0.3 g of polyvinyl pyrrolidone were added to the relatively stable magnesium hydroxide dispersion, and the final dispersion was obtained after uniform dissolution, which was the aqueous phase.
[0067] Preparation of organic phase: 24 g of acrylonitrile and 30.1 g of methyl methacrylate were mixed, and then 0.14 g of 1,4-butanediol dimethacrylate, 0.2 g of diisopropylbenzene peroxide and 6 g of isopentane were added, and then 12 g of rutile titanium dioxide was added and well dispersed to obtain an organic phase.
[0068] Emulsification reaction: Mix the cooled organic phase with the aqueous phase (the volume ratio of the organic phase to the aqueous phase is 1:2), disperse using a high shear emulsifying disperser, then quickly pour into a reactor and seal, deoxygenate with nitrogen and pressurize to 0.5 MPa, heat to 62°C while stirring to react, react for 24 hours, cool to room temperature to terminate the polymerization reaction, and discharge.
[0069] Post-treatment operation: The obtained product was adjusted to pH 2 with 10wt% dilute sulfuric acid to remove magnesium hydroxide deposits on the surface of the microspheres, then rinsed with a large amount of deionized water, filtered, dried at 50°C for 24 hours, and then foamed at 110°C for 2 minutes to obtain thermal expansion microspheres with rutile titanium dioxide as the core.
[0070] 2. Preparation of Radiative Cooling Coating
[0071] 50 parts by weight of heat-expandable microspheres with rutile titanium dioxide as the core and 0.6 parts by weight of wetting agent polyether-modified polysiloxane (BYK-348) were added to 30 parts by weight of water, and then 42 parts by weight of aqueous polyurethane emulsion (Wanhua Tekspro 5215), 0.1 parts by weight of silicone defoamer (BASF FoamStar SI 2292), 0.4 parts by weight of polyurethane leveling agent (Dow RM-3000) and 0.2 parts by weight of associative alkali swelling thickener (Dow DR-72) were added under stirring conditions (speed of 300r / min), and the radiant cooling coating for fabric coating was prepared after stirring for 20 minutes. The radiant cooling coating was evenly coated on the PU coated fabric 2 by a roller coating method using a roller coater. The radiant cooling coating was obtained after drying.
[0072] Example 2
[0073] 1. Preparation of thermally expandable microspheres with rutile titanium dioxide as the core
[0074] Preparation of aqueous phase: 2 g of NaOH was completely dissolved in 50 mL of deionized water, and then an aqueous solution containing 0.1 g of 2-ethylhexyl sulfate sodium salt, 4.8 g of magnesium chloride (MgCl2·6H2O), and 50 mL of deionized water was added under stirring (speed of 400 r / min), and then stirred vigorously (speed of 1500 r / min) for 30 minutes to obtain a relatively stable magnesium hydroxide dispersion, and then 0.5 g of sodium nitrite and 0.1 g of polyvinyl pyrrolidone were added to the relatively stable magnesium hydroxide dispersion, and the final dispersion was obtained after uniform dissolution, which was the aqueous phase.
[0075] Preparation of organic phase: 20 g of acrylonitrile and 20.7 g of methacrylonitrile were mixed, and then 0.077 g of 1,4-butanediol dimethacrylate, 0.1 g of diisopropylbenzene peroxide and 2 g of isopentane were added, and then 5 g of rutile titanium dioxide was added and well dispersed to obtain an organic phase.
[0076] Emulsification reaction: Mix the cooled organic phase with the aqueous phase (the volume ratio of the organic phase to the aqueous phase is 1:1.2), disperse using a high shear emulsifying disperser, then quickly pour into a reactor and seal, deoxygenate with nitrogen and pressurize to 0.4 MPa, heat to 62°C while stirring to react, react for 24 hours, cool to room temperature to terminate the polymerization reaction, and discharge.
[0077] Post-treatment operation: The obtained product was adjusted to pH 3 with 10wt% dilute sulfuric acid to remove magnesium hydroxide deposits on the surface of the microspheres, then rinsed with a large amount of deionized water, filtered and dried at 50°C for 24 hours, and then foamed at 120°C for 1 minute to obtain thermally expandable microspheres with rutile titanium dioxide as the core.
[0078] 2. Preparation of Radiative Cooling Coating
[0079] 41 parts by weight of heat-expandable microspheres with rutile titanium dioxide as the core and 0.4 parts by weight of wetting agent polyether-modified polysiloxane (BYK-348) were added to 10 parts by weight of water, and then 48 parts by weight of aqueous acrylic elastic emulsion (Badefu RS-9900A), 0.3 parts by weight of silicone defoamer (BASF FoamStar SI 2292), 0.1 parts by weight of pH regulator (2-amino-2-methyl-1-propanol (AMP)), 1.3 parts by weight of film-forming aid (alcohol ester twelve), 0.4 parts by weight of silane coupling adhesion enhancer (Momentive Silquest A-1100), 0.4 parts by weight of polyurethane leveling agent (Dow RM-3000), and 0.3 parts by weight of associative alkali swelling thickener (Dow DR-72) were added under stirring conditions (rotation speed of 300 r / min) to prepare a radiant cooling coating for fabric coating. The radiation cooling coating is evenly coated on the PU coated fabric 1 by spraying, and the radiation cooling coating is obtained after drying.
[0080] Example 3
[0081] 1. Preparation of thermally expandable microspheres with rutile titanium dioxide as the core
[0082] Preparation of aqueous phase: 4 g of NaOH was completely dissolved in 50 mL of deionized water, and then an aqueous solution containing 1.5 g of 2-ethylhexyl sulfate sodium salt, 10.2 g of magnesium chloride (MgCl2·6H2O), and mL of deionized water was added under stirring (speed of 400 r / min), and then stirred vigorously (speed of 1500 r / min) for 30 minutes to obtain a relatively stable magnesium hydroxide dispersion, and then 0.5 g of sodium nitrite and 1 g of polyvinyl pyrrolidone were added to the relatively stable magnesium hydroxide dispersion, and the final dispersion was obtained after uniform dissolution, which was the aqueous phase.
[0083] Preparation of organic phase: 30 g of acrylonitrile and 30.4 g of methyl methacrylate were mixed, and then 0.20 g of 1,4-butanediol dimethacrylate, 0.5 g of diisopropylbenzene peroxide and 15 g of isooctane were added, and then 17 g of rutile titanium dioxide was added and well dispersed to obtain an organic phase.
[0084] Emulsification reaction: Mix the cooled organic phase with the aqueous phase (the volume ratio of the organic phase to the aqueous phase is 1:3), disperse using a high shear emulsifying disperser, then quickly pour into a reactor and seal, deoxygenate with nitrogen and pressurize to 0.6 MPa, heat to 62°C while stirring to react, react for 24 hours, cool to room temperature to terminate the polymerization reaction, and discharge.
[0085] Post-treatment operation: The obtained product was adjusted to pH 2 with 10wt% dilute sulfuric acid to remove magnesium hydroxide deposits on the surface of the microspheres, then rinsed with a large amount of deionized water, filtered and dried at 50°C for 24 hours, and then foamed at 130°C for 1 minute to obtain thermally expandable microspheres with rutile titanium dioxide as the core.
[0086] 2. Preparation of Radiative Cooling Coating
[0087] 30 parts by weight of heat-expandable microspheres with rutile titanium dioxide as the core and 0.2 parts by weight of wetting agent polyether-modified polysiloxane (BYK-348) were added to 7 parts by weight of water, and then 60 parts by weight of aqueous polyurethane emulsion (Wanhua Tekspro 5215), 0.9 parts by weight of silicone defoamer (BASF FoamStar SI 2292), and 1.0 parts by weight of adhesion enhancer (Momentive Silquest A-1100) were added under stirring conditions (speed of 300 r / min), and the radiant cooling coating for fabric coating was prepared after stirring for 20 minutes. The radiant cooling coating was evenly applied to the PVC coated fabric by a roller coating method using a roller coater. The radiant cooling coating was obtained after drying.
[0088] The outdoor cooling performance of the radiant cooling coating of different PU coated fabrics and PVC coated fabrics in Examples 1 to 3 was tested (temperature was measured in the same open air natural environment). The results are shown in Figure 1 It can be seen that compared with the blank substrate without radiation cooling coating, each group of radiation cooling coatings showed a good cooling effect, and the temperature drop was about 5 to 20 °C.
[0089] Example 4
[0090] 1. Preparation of thermally expandable microspheres with rutile titanium dioxide as the core
[0091] Preparation of aqueous phase: 3 g of NaOH was completely dissolved in 50 mL of deionized water, and then an aqueous solution containing 0.6 g of 2-ethylhexyl sulfate sodium salt, 7.5 g of magnesium chloride (MgCl2·6H2O), and 50 mL of deionized water was added under stirring (speed of 400 r / min), and then stirred vigorously (speed of 1500 r / min) for 30 minutes to obtain a relatively stable magnesium hydroxide dispersion, and then 0.1 g of sodium nitrite and 0.4 g of polyvinyl pyrrolidone were added to the relatively stable magnesium hydroxide dispersion, and the final dispersion was obtained after uniform dissolution, which was the aqueous phase.
[0092] Preparation of organic phase: 26 g of acrylonitrile and 32.6 g of methyl methacrylate were mixed, and then 0.15 g of 1,4-butanediol dimethacrylate, 0.4 g of diisopropylbenzene peroxide and 12 g of isopentane were added, and then 13 g of organically coated surface-modified rutile titanium dioxide (Chemours R-902+) was added and well dispersed to obtain an organic phase.
[0093] Emulsification reaction: Mix the cooled organic phase with the aqueous phase (the volume ratio of the organic phase to the aqueous phase is 1:2), disperse using a high shear emulsifier, then quickly pour into a reactor and seal, deoxygenate with nitrogen and pressurize to 0.4 MPa, heat to 62°C while stirring to react, react for 24 hours, cool to room temperature to terminate the polymerization reaction, and discharge.
[0094] Post-treatment operation: The obtained product was adjusted to pH 2 with 10wt% dilute hydrochloric acid to remove magnesium hydroxide deposits on the surface of the microspheres, then rinsed with a large amount of deionized water, filtered and dried at 50°C for 24 hours, and then foamed at 120°C for 1 minute to obtain thermal expansion microspheres with rutile titanium dioxide as the core.
[0095] 2. Preparation of Radiative Cooling Coating
[0096] 60 parts by weight of heat-expandable microspheres with rutile titanium dioxide as the core and 1.0 parts by weight of wetting agent polyether-modified polysiloxane (BYK-348) were added to 40 parts by weight of water, and then 55 parts by weight of aqueous acrylic elastic emulsion (Badefu RS-9900A), 0.3 parts by weight of silicone defoamer (BASF FoamStar SI 2292), 0.5 parts by weight of pH regulator (ammonia water) and 0.5 parts by weight of associative alkali swelling thickener (Dow DR-72) were added under stirring conditions (speed of 300 r / min), and the radiant cooling coating for fabric coating was prepared after stirring for 20 minutes. The radiant cooling coating was evenly coated on the woven fabric by spraying. The radiant cooling coating was obtained after drying.
[0097] The outdoor cooling performance of the woven fabric radiant cooling coating in this embodiment was tested, and the results are shown in Figure 2 It can be seen that compared with the blank substrate without coating, the radiation cooling coating shows a good cooling effect, and the temperature drop is about 5 to 15°C.
[0098] Comparative Example 1
[0099] The same as Example 1, except that, in this comparative example, the thermal expansion microspheres with rutile titanium dioxide as the core were not prepared, but the thermal expansion microspheres with rutile titanium dioxide as the core were directly replaced with an equal amount of rutile titanium dioxide when preparing the radiation cooling coating.
[0100] Comparative Example 2
[0101] The same as Example 1, except that, in this comparative example, rutile titanium dioxide was not added when preparing the heat-expandable microspheres, thereby obtaining heat-expandable microspheres with only low-boiling point alkanes as the core; when preparing the radiation cooling coating, the heat-expandable microspheres with rutile titanium dioxide as the core were replaced with an equal amount of heat-expandable microspheres.
[0102] Comparative Example 3
[0103] Same as Example 1, except that the heating temperature in the emulsification reaction step is 80°C instead of 62°C.
[0104] To verify the technical effect of the present invention, the radiant cooling coatings of the above embodiment and comparative example were respectively roll-coated on the surface of non-woven fabrics by a roll coater according to the same process parameters. The temperature difference of the above coatings compared with the uncoated blank non-woven fabrics was tested horizontally under the same open-air sunlight conditions. The radiant cooling coatings of the above embodiment and comparative example were tested for elongation at break according to the type 1 dumbbell test piece specified in GB / T 528-2009; and the peeling strength of the coating was tested according to FZ / T 01010-2012.
[0105] The test results are shown in Table 1, which shows that the coatings of each embodiment have outstanding radiative cooling performance, flexibility and coating adhesion. Comparative Example 1 only relies on the rutile titanium dioxide in the coating to scatter sunlight, and has certain radiative cooling performance; however, the embodiment group can greatly optimize the scattering ability and thus improve the cooling performance by virtue of the refractive index difference of the hollow structure around the titanium dioxide. Comparative Example 2 relies on the elastic effect of the thermally expandable microspheres, and the flexibility and adhesion of the coating are very ideal, but without the rutile titanium dioxide core, the radiative cooling performance is completely limited. Comparative Example 3 was polymerized at 80°C, and although it was able to successfully encapsulate isopentane, it failed to expand when heated and foamed. The three test data results of the unexpanded microspheres are inferior to those of Example 1, highlighting the performance advantages of the thermally expandable microsphere structure of the present invention.
[0106] Table 1
[0107]
[0108] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A radiation cooling coating for fabrics, characterized in that: The raw materials are composed of water-based resin emulsion, core-shell structure functional filler, additives and water; The core-shell structure functional filler is a heat-expandable microsphere with rutile titanium dioxide and low-boiling-point alkane as the core and acrylonitrile-methyl methacrylate copolymer or acrylonitrile-methacrylonitrile copolymer as the shell.
2. The radiation cooling coating for fabric according to claim 1, characterized in that: The rutile titanium dioxide is organically coated surface-modified rutile titanium dioxide, and the low-boiling-point alkane is isopentane or isooctane.
3. The radiation cooling coating for fabric according to claim 1, characterized in that: The aqueous resin emulsion is one of an aqueous polyurethane emulsion and an aqueous acrylic elastic emulsion.
4. The radiation cooling coating for fabric according to claim 1, characterized in that: The auxiliary agent includes at least one of a wetting agent, a defoaming agent, a pH adjusting agent, a film-forming auxiliary agent, a thickener, a leveling agent and an adhesion enhancer.
5. The radiation cooling coating for fabric according to claim 1, characterized in that: The method for preparing the core-shell structure functional filler comprises the following steps: Dissolve sodium hydroxide in water, add a magnesium chloride aqueous solution containing 2-ethylhexyl sulfate sodium salt, stir to obtain a magnesium hydroxide dispersion, then add sodium nitrite and polyvinyl pyrrolidone, stir evenly to obtain an aqueous phase; acrylonitrile and methyl methacrylate are mixed, and then 1,4-butanediol dimethacrylate, diisopropylbenzene peroxide, low-boiling-point alkane and rutile titanium dioxide are added, and stirred evenly to obtain an organic phase; The organic phase is mixed with the aqueous phase, and after being dispersed evenly, the mixture is reacted under pressure, and the mixture is discharged after cooling; The pH value of the product obtained by discharging is adjusted to acidic, and the product is washed, filtered, dried and foamed to obtain the core-shell structure functional filler.
6. The radiation cooling coating for fabric according to claim 5, characterized in that: The molar ratio of sodium hydroxide to magnesium chloride is 2 to 2.1:1; and / or The mass ratio of water, sodium hydroxide, sodium salt of 2-ethylhexyl sulfate, sodium nitrite and polyvinyl pyrrolidone in the aqueous phase is 100: 2-4: 0.1-1.5: 0.01-0.5: 0.1-1; and / or In the mixture of acrylonitrile, methyl methacrylate or methacrylonitrile and 1,4-butanediol dimethacrylate, the molar fraction of acrylonitrile is 55-65 mol % and the molar fraction of 1,4-butanediol dimethacrylate is 0.05-0.2 mol %; and / or The mass ratio of acrylonitrile, dicumyl peroxide, low boiling point alkane and rutile titanium dioxide in the organic phase is 20-30: 0.1-0.5: 2-15: 5-17; and / or The volume ratio of the organic phase to the aqueous phase is 1:1.2-3; and / or The step of adjusting the pH value to acidic is adjusting the pH value to 2-3.
7. The radiation cooling coating for fabric according to claim 5, characterized in that: The process of mixing the organic phase and the aqueous phase, dispersing them uniformly at high speed, and then reacting them under heating and pressurization conditions is as follows: pouring the dispersed materials into a reactor, sealing, deoxygenating with nitrogen and pressurizing to 0.4-0.6MPa, heating to 62°C while maintaining stirring to react, reacting for 24 hours, cooling to room temperature to terminate the polymerization reaction, and discharging the materials.
8. The radiation cooling coating for fabric according to claim 5, characterized in that: The temperature of the foaming treatment is 110-130° C., and the time is 1-2 minutes.
9. A method for preparing a radiation cooling coating for fabrics according to any one of claims 1 to 8, characterized in that: The following steps are involved: Accurately weigh the raw materials according to the weight ratio, add the core-shell structure functional filler into water, add the water-based resin emulsion and the additive under stirring, and obtain the coating; The coating is applied onto a flexible substrate and dried to obtain a radiative cooling coating.
10. The method for preparing the radiation cooling coating for fabric according to claim 9, characterized in that: The flexible substrate includes a fabric or a coated fabric.